2014
DOI: 10.1016/j.pscychresns.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altitude on brain intracellular pH and inorganic phosphate levels

Abstract: Normal brain activity is associated with task-related pH changes. Although central nervous system syndromes associated with significant acidosis and alkalosis are well understood, the effects of less dramatic and chronic changes in brain pH are uncertain. One environmental factor known to alter brain pH is the extreme, acute change in altitude encountered by mountaineers. However, the effect of long-term exposure to moderate altitude has not been studied. The aim of this two-site study was to measure brain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Another possible factor that affects intracellular pH may be mild hyperventilation under hypoxic condition. High‐altitude residents showed higher levels of pH in both arterial blood and brain than did sea‐level residents . This opposite directional drive in pH may dim the pH differences in the study population.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Another possible factor that affects intracellular pH may be mild hyperventilation under hypoxic condition. High‐altitude residents showed higher levels of pH in both arterial blood and brain than did sea‐level residents . This opposite directional drive in pH may dim the pH differences in the study population.…”
Section: Discussionmentioning
confidence: 88%
“…The comparability of spectral data across the two study sites has been validated using phantoms as reported in an earlier publication . Although the same type of scanner manufactured by Siemens and dual‐tuned RF coil were used at both sites, we also monitored the quality of MR spectroscopic imaging by performing repeated 31 P‐MRS scans at both sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy individuals residing at 1370m (Salt Lake City, UT) show reduced inorganic phosphate levels and increased brain pH compared to those residing near sea level (Belmont, MA or Charleston, SC). 56 In rodents, hypobaric hypoxia increases the ratios of cellular metabolites like inositol to total creatine in the frontal cortex, 57 which is compatible with reductions in total creatine level. Accordingly, the women participating in this study may have been more likely than women residing at sea level to respond to the intervention, and, because of reduced basal serotonin synthesis, less likely to develop serotonin syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia and energy starvation might have resulted in the slowing of intracellular pumping of phosphorus, leaving part of the mineral outside. For example, hypobaric hypoxia is associated with reduction of phosphorus content within the brain . Shortage of bioavailable phosphorus within a cell may have impeded ATP production as was recently shown in case of chondrocytes and may have closed circulus vitiosus of detrimental events .…”
Section: Discussionmentioning
confidence: 99%